2013
DOI: 10.3390/molecules18066969
|View full text |Cite
|
Sign up to set email alerts
|

Diels-Alder Reactions of 12-Hydroxy-9(10®20)-5aH-abeo-abieta-1(10),8(9),12(13)-triene-11,14-dione

Abstract: 12-Hydroxy-9(10→20)-5aH-abeo-abieta-1(10),8(9),12(13)-triene-11,14-dione (quinone 2) served as the dienophile in numerous intermolecular Diels-Alder reactions. These cycloadditions were conducted either thermally (including microwave heating) or with Lewis acid activation. While most dienes reacted with quinone 2 in good chemical yield, others were incompatible under the experimental conditions used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Our strategy to prepare salvadione-B is shown in Scheme . We have shown that dienes add to quinone ( S)- 4 from the α-face, thereby creating the requisite relative configurations at C-8, C-9 and C-25 of salvadione-B . The use of triene-selenide 3 in a Diels–Alder reaction raises the question whether it will react as a 2,4- or as a 4,6-disubstituted butadiene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our strategy to prepare salvadione-B is shown in Scheme . We have shown that dienes add to quinone ( S)- 4 from the α-face, thereby creating the requisite relative configurations at C-8, C-9 and C-25 of salvadione-B . The use of triene-selenide 3 in a Diels–Alder reaction raises the question whether it will react as a 2,4- or as a 4,6-disubstituted butadiene.…”
mentioning
confidence: 99%
“…Reactions carried out at reaction temperatures below 70 °C produced Diels–Alder adduct 17 and its regioisomer 18 in a 1:1 ratio. When the reaction temperature was maintained at 90 °C, the rate of the retro-Diels–Alder reaction of triene 17 was faster than the retro-cyloaddition rate of 18 , allowing only selenide 18 to be isolated …”
mentioning
confidence: 99%